Compatibility of polymers to fungi Beauveria bassiana and Metarhizium anisopliae and their formulated products stability - Wenzel Rodrigues, Inajá Marchizeli; Batista Filho, Antonio; Giordano, Isabella Barichello; Denadae, Bárbara Evelin; Fernandes, João Batista; Forim, Moacir Rossi (Acta Scientiarum. Agronomy, 2017)
Stability during storage is a limiting factor in the development and use of bioinsecticides. This study aims to evaluate the compatibility of the entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana with components used in encapsulated formulations and to evaluate shelf-life in formulations with B. bassiana. Sodium alginate and maltodextrin, hemicellulose, and dimethyl sulfoxide solvents were evaluated. Compatibility was evaluated by mixing the components with PDA, and the parameters evaluated were vegetative growth, sporulation and viability. The formulations of fungi were prepared in various concentrations of sodium alginate and then added drop-wise to calcium chloride. To evaluate the stability, formulations were stored at 26.5, 4.0, and -20.0°C. Monthly, samples were taken, and the capsules were placed on Petri dishes with PDA to verify the growth after seven days of incubation. These evaluations were performed by the 12th month. Biopolymers evaluated were compatible with both fungi, exception maltodextrin at 1.5%, which was classified as moderately toxic to B. bassiana. Dimethyl sulfoxide was classified as moderately toxic to B. bassiana at 3.0% and to M. anisopliae at 2.0% and 3.0%. The formulations were stable throughout the 12 months in the conditions evaluated, while for the pure conidia of the fungus, 46% viability in the 6th month at 26.5°C was observed.